Penerapan Konsep Taman Sehat pada Layout Taman Hotel Butik Resor di Kota Batu - Tanuy, Rieka Aprilia; Wilianto, Herman (Jurnal Lanskap Indonesia, 2022)
The stresses of city living cause more people to become aware of and concerned about their health and well-being. People are beginning to look for places to take a holiday, and ecotourism is one of them. Returning to nature is said to be able to replenish the energy that has been expended. The overwhelming demand for open space that promotes a healthy lifestyle in the community has prompted a number of businesses to respond. The hotel's gardens are no longer just a green space. Several hotels have begun to build gardens based on a healthy lifestyle design concept. However, the gardens at these hotels are rarely designed in such a way that they can encourage a healthy lifestyle. As a result, this research looks at how a healthy garden might be used in a boutique resort hotel's environment to promote a healthy lifestyle. On the basis of connected issues, this qualitative research employs an exploratory descriptive approach on the two selected precedents, namely Klub Bunga Boutique Resort Batu, Malang and Park Royal on Pickering, Singapore. The community's demand for a location that can alleviate boredom and stress levels through an interaction with nature is intended to be met by this research. The study's result is a basic guideline for building healthy gardens in boutique resort hotels, while additional attention to the context of site is required.